Percutaneous vertebroplasty with bone cement in cases of thoracolumbar vertebral fractures - Shatursunov, Shahaydar; Sattarov, Alisher; Musaev, Rustam; Baboev, Abduvahob; Kobilov, Aziz (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Occurrence of vertebral fractures in cases of osteoporosis in Uzbekistan is of 15 % in average. Percutaneous vertebroplasty (PV) is a minimally invasive procedure , which is currently used for the treatment of osteoporotic vertebral fractures (OVF). Purpose: to evaluate results of vertebroplasty with bone cement in the cases of compression OVF. Methods: 42 patients (9 male and 33 female, mean age 65 years) with thoracolumbar spine OVF whom PV was performed in 2010-2012. Period of existence of fractures was not less than 3 months. During this period of time conservative treatment was performed. There were none neurological signs in these patients. 30 patients were able to move independently, 10 – with assistance, and 2 were not able to move because of dorsal pain. Localization of lesion was at ThX/LV level. Multiple OVF were in 30 patients. Plan of examination included radiological absorptiometry, X-ray filming, CT and MRI scanning. Pain was assessed by means of visual analogue scale (VAS), and limitations of movement was assessed by means of Roland-Maurice questionnaire. Vertebroplasty was done by only one surgeon under local anesthesia with 1% of lidocaine under X-ray control. We used polymethylmetakrylat with Karl Storz equipment. PV at one level was in 40 patients (10 dorsal and 30 lumbar vertebrae), at two levels was in 2 ones. After PV we prescribed bed rest allowed to walk on the second day after surgery. Patients were prescribed such osteotropic drugs as alendronate sodium (70 mg 1 time per week), Ca (1000 mg daily) and vitamin D3 (400 MYE per day). Results: good results of treatment obtained in 30 patients, satisfactory - in 10, and poor – in 2 ones. After 1 year T-score values increased to 2.7 SD (from -2.3 to 3.5) in average. Before surgery T-score values were -2.9 SD (from -2.9 to -4.0) in average. Average VAS score was 7 (from 6 to 8) before surgery and 3 (from 2 to 4) after surgery. RDQ before surgery was 17.5 (26 to 23) in average, and after one year improved to 12 (from 8 to19) due to pain reduced. In 3 patients penetration of cement into the intervertebral disc, in 1 - into paravertebral tissues, and in 1 – into the spinal canal without any clinical symptoms were revealed. Conclusion: PV is an effective and safe procedure in cases of OVF but selection of patients is crucial to successful outcome.